2023
DOI: 10.1002/ajpa.24701
|View full text |Cite
|
Sign up to set email alerts
|

Sagittal suture strain in capuchin monkeys (Sapajus and Cebus) during feeding

Abstract: Objectives: Morphological variation in cranial sutures is used to infer aspects of primate feeding behavior, including diet, but strain regimes across sutures are not well documented. Our aim is to test hypotheses about sagittal suture morphology, strain regime, feeding behavior, and muscle activity relationships in robust Sapajus and gracile Cebus capuchin primates.Materials and Methods: Morphometrics of sinuosity in three regions of the sagittal suture were compared among museum specimens of Sapajus and Cebu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…As reported in Byron et al . [84], the working-side SPT peaks significantly earlier than the balancing-side SMT and SPT, and the working-side SMT and superficial masseter (all p < 0.05; electronic supplementary material, figure S1 and table S4) in rank order comparisons. These comparisons also suggest the working-side SAT peaks significantly earlier than the balancing-side SPT, which peaks significantly later than the balancing-side SAT (both p < 0.05; electronic supplementary material, table S4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported in Byron et al . [84], the working-side SPT peaks significantly earlier than the balancing-side SMT and SPT, and the working-side SMT and superficial masseter (all p < 0.05; electronic supplementary material, figure S1 and table S4) in rank order comparisons. These comparisons also suggest the working-side SAT peaks significantly earlier than the balancing-side SPT, which peaks significantly later than the balancing-side SAT (both p < 0.05; electronic supplementary material, table S4).…”
Section: Resultsmentioning
confidence: 99%
“…The EMG data were collected using indwelling bipolar fine-wire electrodes following procedures described in Byron et al . [84]. Briefly, the ends of two EMG wires were threaded into a 25-gauge or smaller hypodermic needle, then folded against the needle shaft to create a hook.…”
Section: Methodsmentioning
confidence: 99%
“…As we found in our human models, Behrent et al found the sagittal suture to be placed under medial-laterally directed tension during chewing in macaques, but the findings are limited due to the use of single-element gauges [ 33 ]. The nonhuman primate for which the best in vivo data are available is the capuchin monkey Cebus/Sapajus from Byron et al [ 73 ]. In vivo strains were measured at three sites along the sagittal suture in adult capuchins using rosette strain gages.…”
Section: Discussionmentioning
confidence: 99%
“…They also show that the sagittal suture is not loaded in purely laterally directed tension, as is often assumed, but is subjected to torsion or twisting, probably due to asymmetrical activity of the temporalis muscle. However, the data show that tensile strains are larger at the front of the sagittal suture than the back, and this is associated with greater sinuosity in the anterior suture than more posteriorly [ 74 ]. Conflicting data exists for rat models, such as those reported by Shibazaki et al, who measured the interfrontal suture to be in compression during chewing [ 31 ].…”
Section: Discussionmentioning
confidence: 99%